Precise Activation of Ammonia and Carbon Dioxide by an Iminodisilene. Issue 44 (15th July 2018) - Wendel, Daniel; Szilvási, Tibor; Henschel, Daniel; Altmann, Philipp J.; Jandl, Christian; Inoue, Shigeyoshi; Rieger, Bernhard
Abstract: The activation of NH3 and CO2 is still an ambitious target for multiply bonded sub‐valent silicon compounds. Now, the precise splitting of the N−H bond of ammonia by (Z)‐imino(silyl)disilene1 to give trans‐1, 2‐adduct2 a at low temperatures (−78 °C) is presented. According to DFT calculations, the stereospecific hydroamination follows a similar mechanism as the recently reported anti‐addition of H2 to the Si=Si bond of1 . The aminosilane2 b could also be obtained as the formal silylene addition product under thermodynamic reaction control. By applying low temperatures, the activation of CO2 with1 selectively afforded the cis‐oxadisilacyclobutanone7‐c as [2+2] cycloadduct. By performing the reaction directly at ambient temperatures, a mixture of three different‐sized silacycles (4 –6 ) was observed. Their formation was investigated theoretically and their structures were revealed with separate experiments using1 and the oxygenation agents N2 O and O2 . Abstract : In pursuit of precision : The double donor–acceptor‐type Si=Si bond of a ( Z )‐imino(silyl)disilene was exploited to selectively activate NH3, leading to the corresponding trans ‐1, 2‐adduct under kinetic and the monomeric aminosilane under thermodynamic reaction control. Furthermore, its reactivity toward Lewis acid B(C6 F5 )3 and the oxygen‐atom transfer agents N2 O, O2, and CO2 was elucidated.